2012
DOI: 10.1016/j.mrfmmm.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methyl-donor deficiency on mutation induction and transgenerational instability in mice

Abstract: The effects of methyl-donor deficiency on genome stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 251 publications
(476 reference statements)
0
18
0
Order By: Relevance
“…As mutation analysis was performed in BALB/c x CBA/Ca F 1 hybrid male mice, mutations were scored at both the smaller BALB/c-derived allele (~ 2.5 kb) and the larger (~3.3 kb) CBA/Ca allele. Similar to previous studies of mutation detection at ESTR loci Glen et al, 2008;Abouzeid Ali et al, 2012;Mughal et al, 2012;Voutounou et al, 2012), only novel DNA fragments demonstrating a shift of at least 1 mm comparative to the progenitor allele were scored as de novo ESTR mutants ( Figure 13). Given that the Ms6-hm locus consists of a pentamer repeat sequence (GGGCA) n (Kelly et al, 1989), a 1 mm shift in distance equates to either a gain (insertion) or loss (deletion) of three repeat units for the CBA/Ca allele and two repeat units for the smaller BALB/c allele.…”
Section: Mutation Scoringmentioning
confidence: 57%
See 4 more Smart Citations
“…As mutation analysis was performed in BALB/c x CBA/Ca F 1 hybrid male mice, mutations were scored at both the smaller BALB/c-derived allele (~ 2.5 kb) and the larger (~3.3 kb) CBA/Ca allele. Similar to previous studies of mutation detection at ESTR loci Glen et al, 2008;Abouzeid Ali et al, 2012;Mughal et al, 2012;Voutounou et al, 2012), only novel DNA fragments demonstrating a shift of at least 1 mm comparative to the progenitor allele were scored as de novo ESTR mutants ( Figure 13). Given that the Ms6-hm locus consists of a pentamer repeat sequence (GGGCA) n (Kelly et al, 1989), a 1 mm shift in distance equates to either a gain (insertion) or loss (deletion) of three repeat units for the CBA/Ca allele and two repeat units for the smaller BALB/c allele.…”
Section: Mutation Scoringmentioning
confidence: 57%
“…In contrast, several studies have reported that maternal in utero exposure fails to illicit any effect on transgenerational instability (Barber et al, 2009;Abouzeid Ali et al, 2012). Likewise, the frequency of ESTR mutation of unexposed first generation offspring remained similar to control levels following the administration of a parental methyl-donor deficient diet (Voutounou et al, 2012).…”
Section: Estr Mutation Detection Studiesmentioning
confidence: 58%
See 3 more Smart Citations